Differences in the effectiveness of pineapple consumption and papaya as self cleansing on changes in debris index in students : Study experimental - Zusuan, Indriana; Bakhtiar, Amri; Sari, Widya Puspita (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: An oral cavity disease that is susceptible to attack is caries. According to the 2018 Riskesdas results in Indonesia, caries in children reached 93%. The high rate of caries can be caused by the food choices that children consume, so preventive measures are needed, one of which is by consuming fruits rich in fiber and water such as pineapple and papaya, which act as natural mouth cleansers or self-cleansers.The aim of the research was to determine the disparity in the efficacy of consuming pineapple and papaya as self-cleansing on changes in debris index among students at SDN 10 Sungai Sapih, Padang City. Methods: The research uses a quasi-experimental design with a one-group pretest-posttest design. The total sample consisted of 70 people, with 35 participants consuming pineapple and the other 35 participants consuming papaya. The sampling technique is purposive sampling. The parameter measured is the debris index before and after consumption of pineapple and papaya. Data analysis used frequency distribution and T-test using SPSS 26 software. Results: The results showed that the average debris index before pineapple consumption was 1.583, after which it became 0.674, the difference between the scores was 0.909. The average value of the debris index before consuming papaya was 1.677, decreasing to 0.629, so there was a difference of 1.048. The p-value is 0.00<0.05 for both fruits. Conclusions: There is a difference in the effectiveness of consuming pineapple and papaya for self-cleansing purposes in relation to changes in debris index among students at SDN 10 Sungai Sapih, Padang City. Papaya shows greater effectiveness in reducing debris index scores compared to pineapple.KEYWORDS: pineapple (ananas comosus (L.) Merr.), pawpaw (Carica papaya L.), self cleansing, debris indexPerbedaan efektivitas konsumsi buah nanas dan pepaya sebagai self cleansing terhadap perubahan debris index pada siswa  sdn 10 sungai sapih kota padangABSTRAKPendahuluan: Penyakit rongga mulut yang rentan menyerang adalah karies. Menurut Hasil Riskesdas 2018 di Indonesia, karies pada anak mencapai angka 93%. Tingginya angka karies dapat disebabkan oleh pilihan makanan yang dikonsumsi anak, sehingga diperlukan tindakan pencegahan salah satunya melalui konsumsi buah-buahan yang kaya serat dan air seperti nanas dan pepaya, yang bertindak sebagai pembersih mulut alami atau self cleansing. Tujuan penelitian untuk menganalisis perbedaan efektivitas konsumsi buah nanas dan pepaya sebagai self cleansing terhadap perubahan debris indeks pada siswa Sekolah Dasar. Metode: Penelitian menggunakan desain quasi experimental dengan one-group pretest-posttest design. Sampel keseluruhan terdiri dari 70 orang, dengan 35 peserta mengonsumsi nanas dan 35 peserta lainnya mengonsumsi pepaya. Teknik pengambilan sampel secara purposive sampling. Parameter yang diuji adalah debris indeks sebelum dan sesudah konsumsi nanas dan pepaya. Analisis data menggunakan distribusi frekuensi dan uji T-test menggunakan software SPSS 26. Hasil: Rerata debris indeks sebelum konsumsi nanas sebesar 1,583, sesudahnya menjadi 0,674, dan selisih skor 0,909. Nilai rerata debris indeks sebelum konsumsi pepaya adalah 1,677 menurun menjadi 0,629, sehingga terdapat selisih 1,048. Nilai p-value 0,00<0,05 untuk kedua buah. Simpulan: Terdapat perbedaan efektivitas konsumsi buah nanas dan pepaya untuk tujuan self cleansing dalam kaitannya dengan perubahan debris indeks pada siswa di SDN 10 Sungai Sapih Kota Padang. Pepaya menunjukkan efektivitas yang lebih besar dalam mengurangi skor debris indeks dibandingkan dengan nanas.KATA KUNCI: buah Nanas (Ananas comosus (L.) Merr.), pepaya (carica papaya L.), self cleansing, debris indek